The Impact of the Resort-Based Borobudur Highland Master Plan as an Integrated Tourism Area - siregar, Aisyah Astinadia (Samarinda State Polytechnic, 2023)
Tourism in Indonesia has quite good potential and is one of the sectors that spurs the economy in Indonesia. Development of Borobudur Highland which is included in the five super priority tourist destinations. One of them is the construction of hotels and resorts in the Menoreh Hills, Purworejo Regency, Central Java. The master plan was made as a tourism area plan under the Borobudur Authority Agency (BOB) covering an area of ​​309 hectares (ha). This master plan consists of five zones, namely the exclusive resort zone, the entry gate zone, the adventure zone, the cultural zone and the extreme zone. There are three themes in the development of this area, namely ecotourism, cultural tourism and adventure tourism. The method used is using descriptive qualitative. Data collection techniques through interviews, observation, and documentation. The data analyzed using the SWOT matrix. The results of this research can increase the existence of tourism objects in the Purworejo and Kulonprogo areas to international class that are sustainable, educative, and provide new breakthroughs that have an impact on investment in employment and local products around the area. The threats that can occur are changes in rainwater catchment areas to become prone to landslides, loss of springs, damage to ecosystems due to logging of trees, and disruption of existing flora and fauna habitats.